An activity theory analysis of how management of a private higher education institution interpret and engage with re-accreditation - Reid, Rhiannon Sara (School of Education, 2021)
The aim of this study was to provide an in-depth understanding of how a single private provider conducted an application for re-accreditation in line with the recently revised accreditation framework set out by the Council on Higher Education. This framework aims to promote an integrated approach to accreditation and increased autonomy for higher education institutions with regard to the reaccreditation of programmes. The research unpacked how accreditation was understood and applied within the context of the institution, placing emphasis on understanding the elements that promoted or inhibited quality as well as the tensions and contradictions that arose within this process. The driving question addressed by this research was: How does management within a South African private higher education institution engage with the re-accreditation process? Literature revealed that there is limited research on understanding quality assurance in private higher education in South Africa, and specifically on accreditation. Cultural-historical activity theory (CHAT) was considered the most effective lens to interpret the findings of this study, as research indicates that it is for teasing out the historical and cultural contradictions within as well as between people, tools and the environment within complex educational systems. Multiple data-gathering techniques, including semi-structured in-depth interviews, participant observations and documentation reviews, were conducted. The findings of this study illuminate the critical role of management and their respective interpretations of quality in the shaping of the application for re-accreditation, that balanced quality development and accountability requirements. The study highlighted contradictions and issues that inhibited meaningful engagement with accreditation as well as the enhancement of programme and institutional quality.